1998
DOI: 10.1073/pnas.95.23.13953
|View full text |Cite
|
Sign up to set email alerts
|

K ATP channel inhibition by ATP requires distinct functional domains of the cytoplasmic C terminus of the pore-forming subunit

Abstract: ATP-sensitive potassium (''K ATP '') channels are rapidly inhibited by intracellular ATP. This inhibition plays a crucial role in the coupling of electrical activity to energy metabolism in a variety of cells. The K ATP channel is formed from four each of a sulfonylurea receptor (SUR) regulatory subunit and an inwardly rectifying potassium (K ir 6.2) pore-forming subunit. We used systematic chimeric and point mutagenesis, combined with patch-clamp recording, to investigate the molecular basis of ATP-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
228
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(251 citation statements)
references
References 37 publications
23
228
0
Order By: Relevance
“…Nucleotide-dependent K ATP channel gating was simulated by an allosteric model where: (i) 4 identical binding sites for ATP and ADP co-exist within the octameric stoichiometry of the K ATP channel complex [15,19]; (ii) binding of ATP to the pore-forming Kir6.2 subunit inhibits channel opening [16,17]; (iii) binding of ADP to the regulatory SUR subunit antagonizes ATPbinding to Kir6.2 [18,20,21]. T i and D i (i = 0-4) are channel species with bound ATP and/or ADP.…”
Section: Allosteric Model Of Channel Gatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleotide-dependent K ATP channel gating was simulated by an allosteric model where: (i) 4 identical binding sites for ATP and ADP co-exist within the octameric stoichiometry of the K ATP channel complex [15,19]; (ii) binding of ATP to the pore-forming Kir6.2 subunit inhibits channel opening [16,17]; (iii) binding of ADP to the regulatory SUR subunit antagonizes ATPbinding to Kir6.2 [18,20,21]. T i and D i (i = 0-4) are channel species with bound ATP and/or ADP.…”
Section: Allosteric Model Of Channel Gatingmentioning
confidence: 99%
“…1) [13][14][15]. ATP maintains K ATP channel closure by binding to Kir6.2 [16,17], whereas ATP/ADP interactions with SUR secure the metabolic sensor function of the channel complex (Fig. 1A) [18][19][20].…”
mentioning
confidence: 99%
“…The fast gating kinetics of the channels is determined by an intrinsic structure within the pore-loop that is near the selectivity filter of the Kir6.2 subunit [41,44] . The long last interburst closing kinetics requires ATP binding to the TM2 helices [42,45] .…”
Section: Introductionmentioning
confidence: 99%
“…ATP binds to the cytoplasmic domain of the Kir6.2 subunit [44,47,48] to inhibit the channel [49] . Each Kir6.2 subunit provides one ATP binding pocket, which is constituted by residues R50, I182, K185, R201, and G334 [5,36] .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that engineered K IR 6.x subunits can assemble functional pores in the absence of a SUR, and that their activity is sensitive to ATP [8, 43,150]. Biochemical studies have demonstrated ATP binding to the large C-terminal domain [147,148,151].…”
Section: K Ir 6x Subunits Are Members Of the Inward Rectifier Superfmentioning
confidence: 99%